ANALYSIS OF THE HEALTH OF BANKS USING THE RGEC APPROACH (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) IN SOUTH BORNEO REGIONAL DEVELOPMENT BANKS (BPD) 2014-2018 - Nita Fitria; Shinta Avriyanti (JAPB, 2023)
The latest regulation issued by Bank Indonesia concerning the assessment of the soundness of a bank is contained in Bank Indonesia Circular Letter No. 13/24/DPNP dated October 25, 2011, where the assessment was carried out using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital), which is an update of the CAMELS method. This study aims to: (1) assess the health level of the South Borneo BPD in terms of the 2014–2018 risk profile aspect; (2) assess the health level of the South Borneo BPD in terms of the 2014–2018 good corporate governance (GGC) aspect; (3) assess the health level of the South Kalimantan BPD in terms of the 2014–2018 earnings aspect; (4) assess the health level of the South Borneo BPD in terms of the 2014–2018 capital aspect; and (5) the soundness of the South Borneo BPD in terms of the 2014–2018 RGEC aspect. The research method used is descriptive with a quantitative approach. The research object is the Regional Development Bank (BPD) of South Borneo, using data in the form of 2014–2018 Financial Report documents downloaded from the official website of the Bank of South Borneo. The results of the research on the level of health seen from the aspect of the Bank Kalsel Risk Profile during 2014–2018 were, on average, quite healthy. The level of soundness seen from the GCG (self-assessment) aspect of Bank Kalsel in 2014–2018 was quite good. The level of soundness seen from the earnings aspect using the ROA, ROE, NIM, and BOPO ratios for 2014–2018 is very healthy. The health level seen from the perspective of capital in 2014–2018 is very healthy. Keywords: Bank Soundness Level, RGEC Method